INTEGRASI NILAI KOLABORATIF DAN STRATEGI DALAM PEMBELAJARAN MATEMATIKA MELALUI GAME BANTENG PERTAHANAN DI TAMAN ALAM OLEAN - Nur Hasanah ana (Jurnal Pengabdian Masyarakat Multidisiplin, 2025)
Mathematics is often considered a complicated and boring subject, especially in mathematical logic. The purpose of this study is to integrate collaborative and strategic values ​​into mathematics learning through the traditional game "Benteng Pertahanan" (Defense Fortress) implemented in tutoring activities (bimbel) at Olean Nature Park, Situbondo. The methods used include observation, material guidance, game simulations, direct practice, discussion, and evaluation. The research subjects were 20 elementary and junior high school students. Based on the results of the community service, it shows that this approach is able to increase students' interest, concentration, cooperation, memory, and strategic thinking skills. This contextual learning based on local culture has proven effective in improving mathematical understanding, especially in elementary and junior high school students. with the results of the effectiveness test less than 21%, it is said to be less effective if the percentage value results start from 21% to 40%, it is said to be quite effective if the percentage value results start from 41% to 60%, and it is said to be very effective if the percentage value results start from 81% to 100%.